Propriedades eletrocatalíticas de eletrodos nanoestruturados constituídos por multicamadas metálicas - Freitas Sobrinho, Renato Garcia de (Universidade Federal de São Carlos, 2010)
This work reports the electrochemical and spectroscopic studies of ethylene glycol and ethanol electrooxidation onto Ptpc/(Pt1Ir1)x/Pty, Ptpc/Irx/Pty (where x and y designate different thickness) and alloys Ptpc/(PtxIry)1.5ML (where x and y designate different atomic ratio) metallic multilayer electrodes. About ethylene glycol electrooxidation, it was observed that metallic multilayer electrodes without alloys in the inner layer, i.e. Ptpc/Ir3.0/Pt3.0 exhibited are increase around 175% in the peak current. Using factorial design technique, it was possible to determine that the composition effect of the inner layer was the most significant. Using in situ FTIRRAS, it was observed that the CO2 onset production over Ptpc/Ir3.0/Pt3.0 metallic multilayer electrodes shifted 100mV towards more negative values and its production was increased by approximately 140% compared to Ptpc. During the ethanol electrooxidation, it was observed that the process onset was shifted 200mV towards more negative values over Ptpc/Irx/Pty and the peak current density increased about 375% over Ptpc/Ir1.3/Pt10 compared to Ptpc. The CO2 production was shifted 100mV towards more negative for all Ptpc/Irx/Pty metallic multilayer electrodes, and especially for Ptpc/Ir250/Pt250 the CO2 production increased up to 960%. A complete C-C bond cleavage for ethanol molecule, leading to COL as intermediate and CO2 as final reaction production was for the first time observed in this work. Therefore, no band related to acetaldehyde and acetic acid was observed by in situ FTIRRAS over Ptpc/Ir250/Pt250 metallic multilayer electrodes.
Keywords: Eletrocatálise; Multicamadas metálicas; Eletrodos nanoestruturados; Eletrooxidação de etanol; CIENCIAS EXATAS E DA TERRA::QUIMICA